Categorical ERP repetition effects for human and furniture items in 7‐month‐old infants. Issue 5 (2nd December 2016) - Peykarjou, Stefanie; Wissner, Julia; Pauen, Sabina
Abstract: Behavioural and recent neural evidence indicates that young infants discriminate broad stimulus categories. However, little is known about the categorical perception of humans represented as full bodies with heads and their discrimination from inanimate objects. This study compares infants' brain processing of human and furniture pictures, probing infants' categorization skills with an event‐related potential (ERP) paradigm. Seven‐month‐old infants ( n  = 23) were tested in a rapid repetition ERP paradigm. Trials consisted of two consecutive stimuli: prime and target. Different ERP parameters (Nc, PSW) were compared across human and furniture items and for repeated and unrepeated categories. The PSW was consistently enhanced for unrepeated compared to repeated categories, thus indicating category discrimination. Nc amplitude was enhanced for furniture primes compared to human primes, but not for corresponding targets. In sum, these findings suggest that ERP rapid repetition studies are suitable for probing perceptual category discrimination in infancy. 7‐month‐olds discriminated between humans, presented as full body pictures, and furniture exemplars, but did not seem to prefer either of these categories. Highlights: 7‐month‐olds' ability to categorize humans and furniture items was tested using rapid repetition ERPs. The PSW was enhanced for unrepeated categories, indicating broad categorization. The Nc, indicating neural attention, was not enhanced for humans compared to furniture items.